Spirituality, Cultural Factors, Students’ achievement In Social Studies As Predictors Of Morality Among Secondary School Students In Benue State, Nigeria. - Tyowua, Felix; Adegbile, Prof. J. A (African Journal of Behavioural and Scale Development Research, 2022)
The concept of morality is mostly seeing as a brainchild of people’s religion as well as their cultural formation. This study was necessitated as a result of the rising cases of immorality among youths in our today’s generation; hence, attempts to identify the root causes of such behaviors have been an endless debate among scholars. The study adopted correlational research design, and Multi-stage sampling technique was used to select three hundred and fifteen (315) students from two senatorial districts (Zone A, and Zone C) in Benue State. Four instruments were used for the study; Religiosity and Spirituality scale, Cultural factors questionnaire, social studies achievement test, and Moral Identity Questionnaire. Findings from the study revealed that all the variables jointly predicted morality among junior secondary school students in Benue State significantly. Furthermore, results showed that components of independent variables considered; Spirituality (Beta=0.044, t =0.659, p>0.05), Cultural factors (Beta = -0.092, t = -1.633, p > 0.05), and social studies (0.076, t=1.337, p>0.05) do not significantly predict morality among secondary school students. It was concluded that parents/guardians should take special interest in curbing moral decadence among the youths. When the thought of the youth is modified or transformed their actions will definitely be transformed.